Peran Perbankan Syariah Dengan Prinsip Prinsip Syariah Konvergensi - Septiana, Evy (Berasan: Journal of Islamic Civil Law, 2022)
This research is entitled The Role of Islamic Banking with Convergent Sharia Principles on Indonesia's Socio-Economic Construction. This study aims to determine whether sharia banking and sharia principles in Indonesia are in accordance with Islamic law and to find out how the convergence of sharia principles to the socio-economic construction of Indonesia. The research method used is a normative juridical approach with the data used are secondary data, and the data is analyzed juridically and quantitatively which is then interpreted from the results of data analysis in the form of deductive conclusions. Islamic banks are banks whose activities refer to Islam and in their activities do not charge interest or pay interest to customers. Islamic bank rewards received or paid to the bank, the agreement (contract) contained in Islamic banking must be subject to the terms and pillars of the contract as stipulated in Islamic law. Basically, Islamic banking in Indonesia has not been running in accordance with the rules of sharia law, therefore the Sharia Supervisory Board does not yet have clarity regarding the scientific capacity and capability of its interest in Indonesian economic issues, especially sharia banking. For this reason, there needs to be transparency from the MUI towards Islamic banks regarding the recommended DPS candidates, even if it is necessary there must be a fit and proper test mechanism for DPS candidates, especially those not from academia.